Sunday

March 29, 2015

March 29, 2015

Posted by **Robert** on Thursday, December 22, 2011 at 3:14am.

Let a=b

square both sides to get a^2=b^2

a^2=b*b

Since a=b, then a^2=a*b

Subtract b^2 from both sides a^2-b^2=a*b-b^2

Factor both sides: (a+b)(a-b)=b(a-b)

Divide both sides by (a-b)

(a+b)=b

Since a=b

b+b=b or

2b=b

Divide by b

- ALgebra -
**Reiny**, Thursday, December 22, 2011 at 7:59amYou said "

**Divide both sides by (a-b)**" , but a = b

so you are dividing by zero, which is a no-no in math .

**Answer this Question**

**Related Questions**

Algebra - Why are these algebraic expressions used and explain the logical error...

math - can anyone help me with these 3 problems I am trying to check my ...

Algebra - explain the logical error Square both sides to get a2 = b2

help please - What is the first step in solving the problem, 3x-8/12=9? A) Add 8...

PLEASE HELP ME!!! - What is the first step in solving the problem, 3x-8/12=9? A...

HELP!!!!! - What is the first step in solving the problem, 3x-8/12=9? A) Add 8 ...

maths - i have to make y the subject of this equation: 4t + 7y - 9 = 0 wod it be...

math - I need help figuring out these two questions on euations with integers. -...

Math - Emmy is 12. She writes an equation to find her mother's age, m. m - 12 + ...

algebra - 7/11 - 2x < 3/10; {1/2, 1/3, 1/4, 1/5, 1/6} Rearrange the ...